Discovery of Bangladesh : explorations into dynamics of a hidden nation - Khan, Akbar Ali, 1944- (Dhaka, Bangladesh : University Press Limited, 2001)
Historical development of rural settlements, political instability, and proselytization in Bangladesh.
Includes bibliographical references and index.
GenEd
Keywords: Bangladesh -- History; Bengal (India) -- History